P Penguatan Tata Kelola Pemerintahan Kampung Telaga Daing melalui Pelestarian Nilai Budaya Lokal di Terengganu Darul Iman, Malaysia: Penguatan Tata Kelola Pemerintahan Lokal (BERDAYA : Jurnal Pengabdian Kepada Masyarakat, 2024)
Realizing development goals requires village governance based on local cultural values. Local cultural values in principle contain moral teachings that can support the achievement of development goals through good governance. The dynamics of governance have brought rapid social change, which often leads to a decline in government values in governance. This has led to a loss of knowledge about the beliefs, social values, moral values and cultural practices that have been part of the community's identity. As a result, services provided do not touch the community, irregularities occur, decision-making is increasingly far from local cultural roots, and community participation in government activities decreases. Real steps based on local cultural values are needed. Based on the identification, there are several local cultural values that need to be preserved in governance, namely deliberation, honesty, cooperation, discipline, hard work, obedience to leaders, and respect for tradition as a basis for strengthening village governance. The method of implementing community service is preparation, implementation, evaluation, and program sustainability. Community Service has been carried out well thanks to the support of various parties, marked by an increase in knowledge, implementation of cultural values, harmonization, participation, and collaboration